In Vivo Significance of Kinetic Constants of Tight Binding Reversible Proteinase Inhibitors - Longstaff, Colin (Thrombosis and Haemostasis, 1992)
For a reaction between an enzyme and inhibitor, rate constants and equilibrium constants are both widely used as measures of inhibitor potency. Which one of these two parameters should be used depends on the mechanism of the reaction. Moreover, for biological studies it is not always the overall effectiveness of an inhibitor that is important, but also the rate at which it acts in conditions that may be encountered in vivo. In vitro investigations may be performed to determine the kinetic and thermodynamic constants in an enzyme inhibitor system and to investigate the influence of various other effector biomolecules. However, in translating these results into physiological conclusions, care must be taken that the in vitro experiments have been properly designed and data analysed correctly. This article is an attempt to indicate some of the problems that can be encountered in this process.